Service Life and Durability of Reinforced Concrete Structures Selected Papers of the 8th International RILEM PhD Workshop held in Marne-la-Vallée, France, September 26-27, 2016 - Andrade, Carmen; Gulikers, Joost; Marie-Victoire, Elisabeth; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume contains the proceedings of the 8th International PhD Student Workshop on Service Life and Durability of Reinforced Concrete Structures that was held in Marne-la-Vallée, France, on September the 26th and 27th 2016. Topics discussed in the book are related to durability performance of reinforced concrete, service life modelling, prevention, protection and repair. Reinforced concrete structures may prove to be very durable, however, their gradual degradation over time impairing both serviceability and structural safety is still a matter of great practical concern in view of the large economic consequences for assessment, maintenance and repair. Corrosion of steel reinforcement is considered to be the most detrimental process responsible for structural deterioration. Many studies are in progress to develop a comprehensive engineering approach for assessment of the initiation and the propagation period of corrosion in both uncracked and cracked concrete. Modelling of chloride penetration and carbonation has attracted a great deal of attention in recent years, however, there is still much debate on several essential aspects such as the chloride threshold level. ASR, and acid, sulphate and frost attack and other mechanisms remain important areas of study. In addition, the interaction between different degradation mechanisms requires further understanding. The worskhop was organised under the auspices of RILEM EAC (Educational Activities Committee), with the aim to bring together young researchers in the field of durability of concrete.
Part 1: Concrete properties and initiation period processes -- Effect of LDH nano-flakes on the mechanical and transport properties of lightweight concrete, by Z. Y. Qu, Q.L. Yu, and H.J.H. Brouwers -- Using thymolphthalein for accelerated carbonation testing of high volume fly ash cementitious blends, by Rui Reis, Aires Camões, and Manuel Ribeiro -- Durability and Mechanical Properties of CNT Cement Composites, by Carmen Camacho-Ballesta, Óscar Galao, Francisco Javier Baeza, Emilio Zornoza, and Pedro Garcés -- Advances in coal bottom ash use as a new common Portland cement constituent, by Cristina Argiz, Esperanza Menéndez, and Amparo Moragues -- Part 2: Techniques of characterization of corrosion and degradation -- Numerical Simulations for the detection of leakages in bridge deck membranes through resistivity measurements, by Carla Driessen and Michael Raupach -- Numerical and experimental development of gradient potential measurement for corrosion detection in reinforcedconcrete, by S. Garcia and F. Deby -- Advances in Characterization of Gas Transport in Concrete: Determination of Oxygen Diffusion Coefficient from Permeability Coefficient and Porosity, by P. Linares, C. Andrade, and D. Baza -- Petrographic Study of Siliceous Aggregates. Parametric Calculus of the Reactivity With the Alkalis, by R. García-Rovés Loza, E. Méndez, and N. Prendes Rubiera -- Part 3: Behaviour of corroded structures -- Corrosion-Induced Degradation of Reinforced Concrete Elements: Preliminary Results, by O. Loukil, L. Adelaide, V. Bouteiller, M. Quiertant, T. Chaussadent, F.Ragueneau, X. Bourbon, and L. Trenty -- Part 4: Corrosion prevention and repair techniques -- Development of a test Method for the Durability of Carbon Textiles under Anodic Polarisation, by Amir Asgharzadeh and Michael Raupach -- Corrosion processes of carbonated chloride-contaminated reinforced concrete and electrochemical chloride extraction (ECE) efficiency, by Yolaine Tissier, Véronique Bouteiller, Elisabeth Marie Victoire, Suzanne Joiret, and Thierry Chaussadent. .
Keywords: Building materials; Mechanics, Applied; Building Materials; Structural Materials; Engineering Mechanics